Investigating the effects of typical rowing strength training practices on strength and power development and 2,000 m rowing performance - Gee, T. I.; Caplan, N.; Gibbon, K. C.; Howatson, G.; Thompson, K. G. (Journal of Human Kinetics, 2016)
This study aimed to determine the effects of a short-term, strength training intervention, typically undertaken by club-standard rowers, on 2,000 m rowing performance and strength and power development. Twenty-eight male rowers were randomly assigned to intervention or control groups. All participants performed baseline testing involving assessments of muscle soreness, creatine kinase activity (CK), maximal voluntary contraction (leg-extensors) (MVC), static-squat jumps (SSJ), counter-movement jumps (CMJ), maximal rowing power strokes (PS) and a 2,000 m rowing ergometer time-trial (2,000 m) with accompanying respiratory-exchange and electromyography (EMG) analysis. Intervention group participants subsequently performed three identical strength training (ST) sessions, in the space of five days, repeating all assessments 24 h following the final ST. The control group completed the same testing procedure but with no ST. Following ST, the intervention group experienced significant elevations in soreness and CK activity, and decrements in MVC, SSJ, CMJ and PS (p < 0.01). However, 2,000 m rowing performance, pacing strategy and gas exchange were unchanged across trials in either condition. Following ST, significant increases occurred for EMG (p < 0.05), and there were non-significant trends for decreased blood lactate and anaerobic energy liberation (p = 0.063 - 0.086). In summary, club-standard rowers, following an intensive period of strength training, maintained their 2,000 m rowing performance despite suffering symptoms of muscle damage and disruption to muscle function. This disruption likely reflected the presence of acute residual fatigue, potentially in type II muscle fibres as strength and power development were affected.